Parentalidade e terapia cognitivo-comportamental : um estudo com pais de crianças na terceira infância - Pereira, Mariana Piotrowski (My University, 2026)
This dissertation aimed to analyze the articulation between parental characteristics and the exercise of parenting among parents of children in middle childhood. The study was developed through a qualitative and exploratory approach, with a multiple case study design and the complementary use of quantitative instruments. Five mothers or caregivers of children aged 6 to 11 years, enrolled in a municipal public school, participated in the research. Data collection included semi-structured interviews, anamnesis, the Cognitive Conceptualization Diagram, the Personality Factor Battery, the Beck Anxiety Inventory, the Beck Depression Inventory-II, and the Parenting Styles Inventory, in addition to psychoeducation and feedback meetings grounded in Cognitive Behavioral Therapy. The qualitative data were analyzed through Thematic Analysis. The qualitative results indicated that the participant?s parenting experiences were crossed by feelings of insecurity, self-demand, guilt, emotional overload, and difficulties in self-regulation, especially when facing challenges related to child behavior management and the consistent establishment of limits. The analysis resulted in six central themes: insecurity and self-demand in the exercise of parenting; emotional overload and challenges in maternal self-regulation; challenges in child behavior management and limit-setting; child vulnerabilities and concerns about child development; life trajectories, trauma, and losses crossing the maternal experience; and affective bonding and protective resources in the parenting experience. The quantitative results showed variability in anxiety levels and depressive symptoms, a predominance of high neuroticism in part of the participants, and the coexistence of positive parenting practices with indicators of difficulty in consistently establishing limits. The integration of the findings demonstrated that parenting is crossed by emotional, historical, sociocultural, and relational dimensions and cannot be understood merely as a set of educational practices. As a technical product, a podcast was developed and published on the UCSPLAY platform, expanding the social reach of the research. It is concluded that parenting interventions grounded in Cognitive Behavioral Therapy may favor reflection, psychoeducation, and the strengthening of more conscious, consistent, and sensitive practices toward children's needs. [resumo fornecido pelo autor]
Esta dissertação teve como objetivo analisar a articulação entre as características parentais e o exercício da parentalidade, com pais de crianças na terceira infância. O estudo foi desenvolvido a partir de uma abordagem qualitativo-exploratória, com delineamento de estudo de casos múltiplos e o uso complementar de instrumentos quantitativos. Participaram cinco mães ou responsáveis por crianças de 6 a 11 anos, matriculadas em uma escola público-municipal. A coleta contemplou entrevista semiestruturada, anamnese, Diagrama de Conceitualização Cognitiva, Bateria Fatorial de Personalidade, Inventário de Ansiedade de Beck, Inventário de Depressão de Beck-II e Inventário de Estilos Parentais, além de encontros de psicoeducação e devolutiva, fundamentados na Terapia Cognitivo-Comportamental (TCC). Os dados qualitativos foram analisados por meio da Análise Temática. Os resultados qualitativos indicaram que a experiência parental das participantes foi atravessada por sentimentos de insegurança, autocobrança, culpa, sobrecarga emocional e dificuldades de autorregulação, especialmente diante dos desafios, no manejo comportamental-infantil e na sustentação de limites. A análise resultou em seis temas centrais: insegurança e autocobrança no exercício da parentalidade; sobrecarga emocional e desafios de autorregulação materna; desafios no manejo comportamental infantil e na sustentação de limites; vulnerabilidades infantis e preocupações com o desenvolvimento da criança; trajetórias de vida, traumas e perdas, atravessando a experiência materna; e vínculo afetivo e recursos protetivos, na experiência parental. Os resultados quantitativos evidenciaram variabilidade, nos níveis de ansiedade e sintomas depressivos, predomínio de neuroticismo elevado, em parte das participantes e coexistência de práticas parentais positivas, com indicadores de dificuldade, no estabelecimento consistente de limites. A integração dos achados demonstrou que a parentalidade é atravessada por dimensões emocionais, históricas, socioculturais e relacionais, não podendo ser compreendida apenas como um conjunto de práticas educativas. Como produto técnico, foi desenvolvido e divulgado um podcast na plataforma UCSPLAY, ampliando o alcance social da pesquisa. Conclui-se que intervenções parentais, fundamentadas na TCC, podem favorecer a reflexão, a psicoeducação e o fortalecimento de práticas mais conscientes, consistentes e sensíveis às necessidades infantis. [resumo fornecido pelo autor]
Keywords: Pais e filhos - Psicologia; Parentalidade; Terapia cognitiva; Parent and child - Psychology; Parenting; Cognitive therapy